Semantic Shift of the Noun under Subordinate Bilingualism - Pažūsis, Lionginas (Kalbotyra, 1981)
Semantic shift, or loanshift extension (in Haugen’s terminology) of the noun is studied under conditions of subordinate bilingualism. The linguistic corpus elicited from Lithuanian periodicals in the USA and Canada as well as from the speech of immigrants whose primary language, Lithuanian (L1), has for several decades been in contact with American English (L2) yields the following generalizations: (1) In the case of multiple lexical units (i. e. derivative and compound nouns), an identical inner form (i. e. an identical arrangement of synonymous morphemes) may also be a point of contact which together with synonymy works in creating the extension of meaning. (2) Interlingual identification of lexemes may also be convergent or divergent (as in diaphonic identification), but in either case it leads to the adjustment of whole synonymic groups of nouns of the two languages. (3) For a big group of Lithuanian nouns, semantic shift is accompanied by transfers “mass noun count noun”. (4) Semantic interference of the L2 noun sometimes manifests itself only by removing some combinatorial semantic restrictions which apply to the synonymous noun in L1. (5) Some nouns in L1 acquire metaphoric and metonymic meanings of L2 nouns. (6) Homologous extension of meaning is more intensive and extensive than synonymous extension of meaning.